Brazilian Digital Women Artists: Giselle Beiguelman and Vitória Cribb in the First Collection of Digital Arts of a Public Brazilian Art Museum - Marcella Nicoli Sousa Imparato; Ana Avelar; Tânia Sulzbacher; Ana Roman (Journal of Science and Technology of the Arts)
This article explores Giselle Beiguelman’s and Vitória Cribb’s works at the ARTEMIDIAMUSEU collection from the National Museum of the Republic by the insightful analyses of Griselda Pollock and Jennifer Way, who, respectively, questioned the omission of female artists within Avant-Garde narratives and explored the interplay between technology and feminism in digital art. By examining their perspectives, we propose a dialogue between Pollock and Way's essays on this theme while exploring the works of two Brazilian digital women artists.